Pengaruh Latar Belakang Pendidikan, Tingkat Religiusitas dan Kesesuaian Jurusan Terhadap Kinerja Karyawan Pada Bank Muamalat Indonesia Cabang Bekasi - Hanif, Annisa Fitria; Rahmawati, Rafika (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2021)
This study aims to determine the effect of educational background, level of religiosity, andsuitability of the department on employee performance at the Bank Muamalat Indonesia Bekasi branch.The independent variable consists of Educational Background, Religiosity Level, and DepartmentSuitability, while the dependent variable is Employee Performance. This study uses primary dataobtained from the questionnaire or questionnaire that has been filled in by all employees of BankMuamalat Indonesia Bekasi Branch who were sampled. The analytical methods used in this researchare the Data Instrument Test (Validity and Reliability Test), Multiple Linear Regression Analysis,Classical Assumption Test (Normality Test, Multicollinearity Test, and Heteroscedasticity Test), andHypothesis Test (T-Test, F-Test, and Coefficient of Determination). From the results of the t-test, itcan be concluded that partially the variables of Educational Background, Religiosity Level, andDepartment Suitability (Dummy) have a positive and significant effect on Employee Performance.And from the results of the F-test, it can be concluded that simultaneously the variables of educationalbackground, level of religiosity, and conformity of the department have a positive effect on employeeperformance.